PENGGUNAAN EKSTRAK DAUN SRIKAYA (ANNONA SQUAMOSA) SEBAGAI PENGENDALI JAMUR FUSARIUM OXYSPORUM SECARA IN VITRO - Purwita, Ayu Anggun; Indah, Novita Kartika; Trimulyono, Guntur (LenteraBio: Berkala Ilmiah Biologi, 2013)
This study aimed to determine the phytochemical profile of srikaya extract qualitatively and the antifungal activities srikaya leaves extract to inhibition on the growth of Fusarium oxysporum and find out the optimal concentration of srikaya leaves extract on inhibiting the F. oxysporum growth. The study were designed by randomized completely design with one factor treatments with 5 concentration.Antifungal activity test to be used solid dilution method. Concentration include 0% (control), 5%, 5.5%, 6%, and 6.5%. Each treatment was repeated with four replications. Observation was conducted after incubation for 7 days at room temperature. The parameters observed was inhibition F. oxysporum growth with indicated size of the diameter mycelial colony. The results showed that the srikaya leaves extract had an inhibitory effect on mycelial colony A. flavus growth. Optimum concentration in this study was 6.5% concentration because it can inhibit the growth of F. oxysporum with an average of 2,84cm ± 0,30 dimater colonies and the percentage inhibition is 60%.